Knowledge Management Policies Options - Gopinath, M. A. (Journal of Information and Knowledge, 2014)
Presents vision of corporate planning, organization, resourceing and implementing various products and services using a variety of alternative policies of knowledge management. Implication of these are presented in eight phased steps with overlapping implications.